Morphological characters of root and yield of three cocoa (Theobroma cacao L.) clones in the field with dead-end trench - Canggih Nailil Maghfiroh; Eka Tarwaca Susila Putra (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
Cocoa (Theobroma cacao L.) is a perennial crop originated from tropical regions, divided into Criollo, Forastero, and Trinitario. Demand for cocoa has increased, but the productivity is still low. The increase in production could be achieved by improving crop management and using superior clones. RCC-70, RCC-71, and KKM-22 are recommended as the superior cocoa clones. Dead-end trench can reduce erosion and surface run-off as well as improve rooting and soil organic matter sequestration. The objectives of this research were to study the effects of dead-end trench application on morphological characters of roots and yields of three cocoa clones and to determine which cocoa clone(s) performed a signifificant yield increase with the application of dead-end trench. The research was conducted in August 2018–April 2019 at Pagilaran Ltd. cocoa plantation in North Segayung Production Unit, subdistrict Tulis, Batang, Central Java. The experiment was arranged in a randomized complete block design with two factors and three replications as block. The first factor was dead-end trench application (with and without dead-end trench application) and the second factor was cocoa clones (RCC-70, RCC-71, and KKM-22). This study showed that application of dead-end trench and clones significantly increased root fresh weight, root dry weight, seed fresh weight, and seed dry weight, but had no significant effect on fruit diameter, fruit length, root length, and root surface area. RCC-70 clone, coupled with the application of dead-end trench, resulted in the highest seed dry weight compared to RCC-71 and KKM-22 clones.